Use of Laparoscopic and Laparotomic J-Plasma Handpiece in Gynecological Malignancies: Results From A Pilot Study in A Tertiary Care Center - Gueli Alletti, Salvatore; Rosati, Andrea; Capozzi, Vito Andrea; Pavone, Matteo; Gioè, Alessandro; Cianci, Stefano; Chiantera, Vito; Vizzielli, Giuseppe; Scaglione, Giulia; Fagotti, Anna; Scambia, Giovanni (Frontiers in Oncology, 2022)
Abstract Introduction The J-Plasma has been recently introduced in the portfolio of surgical community with different intrinsic characteristics aimed to further reduce the thermal effect and enhance precision when compared to standard radiofrequency. The present study aimed to investigate the role of this new technology in different conditions of gynecological carcinomatosis characterized by the indication for regional peritonectomy and/or ablation, either in laparotomy (LPT) and in laparoscopy (LPS), in the context of a modern personalized approach to the surgical management of gynecological malignancies. Material and methods From January 2019 to April 2019, 12 patients were selected for this prospective pilot study at the Division of Gynecologic Oncology, Fondazione Policlinico Universitario A. Gemelli IRCCS in Rome. In this single surgeon experience the inclusion criteria were: histologically proven advanced ovarian/endometrial cancer, primary or interval debulking surgery, and intraoperative indication for regional peritonectomy. 6 patients were treated by LPS(Group1) and 6 by LPT(Group2). Results In Group1 the indication for debulking surgery was in 4 cases an interval debulking surgery and 2 advanced endometrial cancer. All patients in Group 2 underwent primary debulking surgery for advanced ovarian cancer. The whole cohort achieved a complete tumor excision after surgery. The median OT and median EBL were 195min and 100ml in Group 1, and 420 min and 500 ml in Group 2. The median hospital stay was 4 days in Group1 and 13 days in Group2, respectively. No intra and postoperative complications were registered within 60 days after surgery. Conclusions J-Plasma allows to approach delicate maneuvers on viscera, mesentery and blood vessels with a high degree of safety and precision thanks to its limited vertical and lateral thermal spread, favoring the surgeon to push ever higher the cytoreduction/morbidity tradeoff. The use of J- PLASMA in cytoreductive surgery could also increase the range of possible minimally invasive procedures narrowing the technical distance with the open technique, and thus contributing to design a personalized surgical strategy for each patient in different scenarios of peritoneal carcinomatosis.